PENGEMBANGAN MODEL PEMBELAJARAN BACA-TULIS PERMULAAN DALAM PERSPEKTIF EMERGENT LITERACY - Hasanah, Muakibatul (LITERA, 2015)
Abstract This study aims to develop a model for the learning of early reading-writing to improve students' reading-writing competencies. The research data were the results of a study of an early reading-writing curriculum, those of a survey on the implementation of and suggestions for the learning of early reading-writing at elementary schools, and those of a tryout of the prototype of a model for the learning of early reading-writing. The study produced: (1) a model of a guideline for the learning of early reading-writing divided into the essence of early reading-writing and strategies in the learning of early readingwriting in the emergent literacy perspective and (2) a model of an early reading-writing magazine using the performance standard with language characteristics, contents, and techniques.